A model for planning the product portfolio and launch timings under resource constraints. Issue 15 (3rd August 2018) - Dash, Binay; Gajanand, M.S.; Narendran, T.T.
Abstract : Product design is increasingly becoming a critical function in many organisations having significant impact on their performance. It aims at the selection of a near-optimal mix of products and attribute-levels to offer in the target market. The standard product portfolio planning approach has focused on selecting optimum product profiles based on part-worth utility data. However, given that product development happens in multiple stages, combining the product definition decisions with the product development feasibility will provide organisations with a more inclusive and global solution. This paper considers a resource-constrained environment with a multi-stage product development cycle and presents an approach for helping an organisation to select the definitions of products for its product portfolio and the feasible launch timings. The proposed framework will aid product managers and researchers to identify and evaluate alternative product definitions using a Mixed Integer Linear Programming model in order to determine the alternatives which best balance product features and product development.